Covid-19: A critical time for cross-sector social work care management. (7th February 2021) - Franceschini, Dana; Grabowski, Jessica; Sefilyan, Ester; Moro, Teresa T.; Ewald, Bonnie
ABSTRACT: Covid-19 has profoundly impacted social work and has exposed the existing inequities in the health care system in the United States. Social workers play a critical role in the pandemic response for historically marginalized communities and for those who find themselves needing support for the first time. Innovative approaches to care management, including the Center for Health and Social Care Integration (CHaSCI) Bridge Model of transitional care provides a foundation from which social workers can rise to meet these new challenges.